1978
DOI: 10.1037/0022-3514.36.7.767
|View full text |Cite
|
Sign up to set email alerts
|

When pleasure begets pleasure: Recipient responsiveness as a determinant of physical pleasuring between heterosexual dating couples and strangers.

Abstract: Contrary to the well-documented notion that positive verbal responses reinforce behavior, research on physical pleasuring has demonstrated that positive verbal 'responsiveness from a recipient of pleasurable vibrations inhibits, rather than facilitates, heterosexual pleasuring. The present research sought to clarify the role of recipient responsiveness in interpersonal pleasuring through comparison of established dating couples with ad hoc pairs. Using the pleasure paradigm developed by Davis, Rainey, and' Bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…For example, in the present study high selfmonitors are more contingently responsive to the behavior of their partners than are low self-monitors (see also Ickes & Barnes, 1977, 1978. Since contingent responsiveness can induce feelings of acquaintanceship and attraction (Davis & Martin, 1978;Davis & Perkowitz, 1979), it may be that high selfmonitoring persons are strategically responsive. That is, high self-monitors may believe contingent responsiveness leads to more positive interaction outcomes.…”
Section: Discussionmentioning
confidence: 49%
“…For example, in the present study high selfmonitors are more contingently responsive to the behavior of their partners than are low self-monitors (see also Ickes & Barnes, 1977, 1978. Since contingent responsiveness can induce feelings of acquaintanceship and attraction (Davis & Martin, 1978;Davis & Perkowitz, 1979), it may be that high selfmonitoring persons are strategically responsive. That is, high self-monitors may believe contingent responsiveness leads to more positive interaction outcomes.…”
Section: Discussionmentioning
confidence: 49%
“…than approval avoiders; and furthermore, "recognition" scores were positively correlated with approval actually received from subjects' naive partners. Finally, research on physical pleasuring (Davis & Brock, in press;Davis & Martin, 1978;Davis, Rainey, & Brock, 1976) has shown that attraction to a recipient of physical pleasure is facilitated by responsiveness. Recipients who responded to receiving pleasure (by expressing enjoyment) were liked better than those who remained silent.…”
Section: Empirical Evidencementioning
confidence: 99%
“…The hypothesis that low-and high-guilt individuals have different views regarding the appropriateness of interpersonal pleasuring offers many possibilites for future research. As just one example, Davis and Martin (1978) recently examined interpersonal pleasuring in dating and nondating couples. They found, as predicted, that subjects gave more pleasure to dates than to strangers.…”
Section: Discussionmentioning
confidence: 99%